Early humans - Wilkinson, Philip, 1955-; King, Dave (Photographer); Dorling Kindersley, Inc. (London ; New York : DK Publishing, Inc., 2005)
Text and photographs present a description of early humans, their origins, their tools and weapons, how they hunted and foraged for food, and the role of family life, money, religion, and magic.
-- Human or ape? -- Prehistoric food -- Toolmakers -- Flintworking -- Moving northwards -- Coming of fire -- Life in the Ice Age -- Ice-Age hunters -- Modern humans -- First artists -- Hunting and gathering -- Desert hunters -- Tilling the soil -- Clothing and fabrics -- Skin deep -- Magic -- Death and burial -- Ancient writing -- Bronzeworking -- Beauties of bronze -- Bronze-Age warrior -- Iron-Age finery -- Life in the Iron Age -- Men of iron -- Ancient China -- Small change -- Central Americans -- North Americans -- Digging up the past -- Did you know? -- Who's who? -- Find out more -- Glossary -- Index.
At head of title: Eyewitness.
"Discover how the world's first people lived-- from cave dwellings to the tools of the Iron Age"--Cover.
Includes index.
Keywords: Prehistoric peoples -- Juvenile literature; Civilization, Ancient -- Juvenile literature